Rhizosphere Microbiome of Arabica Coffee (Coffea arabica L.) Analyzed Using Oxford Nanopore 16S Sequencing - Nate, Selvia Pinte; Lubis, Syafrina Sari (Jurnal Biologi Tropis, 2025)
The rhizosphere microbiome plays a key role in nutrient cycling, soil structure, and plant health in Coffea arabica. This study analyzed the bacterial community composition of Arabica coffee rhizosphere soil from Tawar Miko, Aceh Tengah, using full-length 16S rRNA sequencing on the Oxford Nanopore platform. Taxonomic profiling revealed ten dominant phyla, including Pseudomonadota (43.77%), Acidobacteriota (18.17%), Planctomycetota (11.23%), Actinomycetota (5.81%), Myxococcota (4.08%), Bacteroidota (3.35%), Bacillota (2.86%), Thermodesulfobacteriota (2.69%), and Nitrospirota (2.26%). At the genus level, the most abundant taxa were Vicinamibacter (8.61%), Bradyrhizobium (4.14%), Brevitalea (4.03%), Pseudolabrys (2.64%), Nitrospira (2.26%), Acidibacter (1.97%), Streptomyces (1.76%), Sandaracinobacter (1.70%), and Paraburkholderia (1.57%). Species-level assessment indicated that Bradyrhizobium sp. was the most abundant, followed by Vicinamibacter sp., Brevitalea sp., Nitrospira sp., Paraburkholderia sp., Pseudolabrys sp., and Acidibacter sp., while low-abundance species (<3%) included Streptomyces sp. and Sandaracinobacter sp. These dominant species contribute to nitrogen fixation, nitrite oxidation, organic matter degradation, hydrocarbon metabolism, and natural biocontrol activity. The balanced distribution across taxa indicates a stable and functionally complementary microbial community that supports soil health and enhances the growth of Arabica coffee in highland agroecosystems.